2024
DOI: 10.1002/ehf2.14744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epicardial adipose tissue on cardiac function and morphology in patients with diastolic dysfunction

Alexander Schulz,
Sören J. Backhaus,
Torben Lange
et al.

Abstract: AimsThis study aimed to identify the impact of increased epicardial adipose tissue (EAT) and its regional distribution on cardiac function in patients with diastolic dysfunction.Methods and resultsSixty‐eight patients with exertional dyspnoea (New York Heart Association ≥II), preserved ejection fraction (≥50%), and diastolic dysfunction (E/e′ ≥ 8) underwent rest and stress right heart catheterization, transthoracic echocardiography, and cardiovascular magnetic resonance (CMR). EAT volumes were depicted from CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In this study, the LV eccentricity was not related to body mass index, subcutaneous fat, visceral fat, or pulmonary vascular resistance and exercise did not modify the cardio-mechanical interaction [103]. Patients with diastolic dysfunction and increased EAT show more pronounced signs of diastolic functional failure and adverse structural remodeling [104]. Despite similar morphological characteristics, patients with high EAT show significant cardiac functional impairment, in particular in the atria, indicating that regionally increased EAT directly induces atrial functional failure [104] (Figure 1).…”
Section: The Pericardial/epicardial Adipose Tissue and Hfpefmentioning
confidence: 46%
See 3 more Smart Citations
“…In this study, the LV eccentricity was not related to body mass index, subcutaneous fat, visceral fat, or pulmonary vascular resistance and exercise did not modify the cardio-mechanical interaction [103]. Patients with diastolic dysfunction and increased EAT show more pronounced signs of diastolic functional failure and adverse structural remodeling [104]. Despite similar morphological characteristics, patients with high EAT show significant cardiac functional impairment, in particular in the atria, indicating that regionally increased EAT directly induces atrial functional failure [104] (Figure 1).…”
Section: The Pericardial/epicardial Adipose Tissue and Hfpefmentioning
confidence: 46%
“…more pronounced signs of diastolic functional failure and adverse structural remodeling [104]. Despite similar morphological characteristics, patients with high EAT show significant cardiac functional impairment, in particular in the atria, indicating that regionally increased EAT directly induces atrial functional failure [104] (Figure 1). Recently, it has been shown that in HFpEF patients obesity and epicardial adiposity are associated with hemodynamic signs of pericardial constraint [106], and 73% of them had a square root sign [106].…”
Section: The Pericardial/epicardial Adipose Tissue and Hfpefmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effects of GLP-1 RAs on HFpEF could be related to the alteration of epicardial adipose tissue (EAT) [132]. Evidence suggests that individuals with diastolic dysfunction have increased epicardial adipose tissue, which could lower peak oxygen consumption and worsen exercise tolerance [133]. Using liraglutide over 6 months, EAT thickness was significantly reduced from 9.6 to 6.26 mm versus no change in the metformin arm [134].…”
Section: Effects Of Glp-1 Ra On Heart Failurementioning
confidence: 99%